A Troubling Story: Insurance and Medical Research in Saskatchewan - Harold Merskey; Robert W Teasell (Pain Research and Management)
It is standard teaching that medicine and health care function in a social setting, and the pain literature is full of material on social and psychological factors. In Pain Research & Management, we drew attention to the impact of social influences on medical thinking and the readiness with which sections of the medical profession sided with paymasters for insurance companies (1). At that time, we were well aware of the most troubling story in decades in the fields of pain, insurance and medical research (2,3). In her commentary in this issue of Pain Research & Management, Lorie Terry (pages 101 to 106) provides information about why the scientific commentators have been radically critical of an article by Cassidy et al, published in The New England Journal of Medicine (2), on the basis of both internal evidence and additional information that accrued, some of which was available at the time of the article's publication and some of which subsequently became public.